Detrital Subsidies in the Diet of Mytilus edulis; Macroalgal Detritus Likely Supplements Essential Fatty Acids - Both, Adrianus; Byron, Carrie J.; Costa-Pierce, Barry; Parrish, Christopher C.; Brady, Damian C. (Frontiers in Marine Science, 2020)
Detritus is a frequent, poorly defined, component of bivalve growth and carrying capacity models. The purpose of this study was to determine the proportional contributions of detrital material derived from primary producers (phytoplankton, macroalgae, Spartina alterniflora, and oak) to particulate organic matter (POM) and blue mussel’s (Mytilus edulis) diet within a temperate bay (Saco Bay, ME USA). We assessed which detrital sources, if any, warranted incorporation into modeling efforts. Stable isotopes (δ13C and δ15N) and fatty acid biomarkers (FA) of mussels, size fractionated (<100 µm) POM, and primary producer endmembers (phytoplankton, Saccharina latissima, Ascophyllum nodosum, Chondrus crispus, Spartina alterniflora and oak leaf litter) collected between 2016 and 2017 were used to estimate endmember contributions to POM and mussel diets. Based on FAs dinoflagellates were the most abundant phytoplankton in Saco Bay, even during the fall diatom bloom. Diatoms within the bay were primarily centric, but pennate diatoms were at times present in the water column (e.g. in September). Following abundances of dinoflagellates, and centric and pennate diatoms, 22:6ω3 (DHA) was the most abundant essential FA (8.6 ± 0.1% total FAs), followed by 20:5ω3 (EPA: 7.0 ± 0.1%) and 20:4ω6 (ARA: 0.3 ± 0.1%). On average, phytoplankton derived organic matter contributed 22.1 ± 0.3% of the total POM in the bay. The concentration of non-fresh phytoplankton organic matter, or remaining organic matter (REMORG), was positively correlated with all endmember biomarkers. However, the proportion (%) of vascular plant, macroalgal, and detrital FAs was negatively correlated with the concentration of REMORG. This finding suggests in periods of low productivity, vascular plant and macroalgal detritus are proportionally more important contributors to POM. Mussels were broad spectrum omnivores, consuming phytoplankton, zooplankton, and detrital material. Detrital contributions to mussel diets were important (minimum of 16% of diet). Although small, macroalgae’s dietary contribution (8%) to M. edulis may be important. Macroalgal detritus contained essential FAs (20:5ω3 and 20:4ω6) that could supplement mussel diets, as M. edulis in Saco Bay were likely limited by 20:5ω3. Consideration of how macroalgal detritus affects the availability of essential FAs in POM may be useful to incorporate into aquaculture site selection.